2023
DOI: 10.7759/cureus.48918
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Comparative Analysis of Platelet-Rich Plasma and Serum Prepared Using a Commercially Available Centrifugation Kit

Takayuki Okumo,
Atsushi Sato,
Kanako Izukashi
et al.

Abstract: Background Platelet-rich plasma (PRP) is an autologous product prepared by centrifuging whole blood. PRP is reported to have high tissue repair potential and anti-inflammatory properties. Recently, PRP has become a potential treatment option for osteoarthritis, contributing to pain relief and locomotive improvement. However, the underlying therapeutic mechanisms and key biochemical factors in PRP remain unclear. This study aimed to estimate the major factors for tissue repair involved in PRP treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
1
Order By: Relevance
“…It also downregulates TNF-α and IL-1β and matrix metalloproteinases [ 40 ]. The results of this hemocomponent factor effect study differed from those of Gallego et al [ 41 ], who found no significant differences in IL-10 levels between PRP and plasma, although in a human PRP study, differences were found in the levels of this cytokine between PRP and serum [ 42 ]. However, the most important finding related to the effect of the hemocomponent factor in the present study was the fact that IL-10 concentrations were better preserved in CI-PLs than in TIPLs, which could indicate that extreme temperature changes may denature this cytokine [ 29 ].…”
Section: Resultscontrasting
confidence: 97%
“…It also downregulates TNF-α and IL-1β and matrix metalloproteinases [ 40 ]. The results of this hemocomponent factor effect study differed from those of Gallego et al [ 41 ], who found no significant differences in IL-10 levels between PRP and plasma, although in a human PRP study, differences were found in the levels of this cytokine between PRP and serum [ 42 ]. However, the most important finding related to the effect of the hemocomponent factor in the present study was the fact that IL-10 concentrations were better preserved in CI-PLs than in TIPLs, which could indicate that extreme temperature changes may denature this cytokine [ 29 ].…”
Section: Resultscontrasting
confidence: 97%